La adaptación como proceso inicial en el desarrollo socioafectivo de los niños y niñas de educación inicial del Centro Educativo Rotary Club Machala Moderno y el Centro de Educación Básica Presidente Jaime Roldos Aguilera de la ciudad de Machala, año 2012. - Herrera Campoverde, Luz Moraima (2013)
This investigative work is to analyze the factors that impact in the adaptation like initial process in the development affective partner of the children and girls of initial education for such a reason my topic THE Adaptation LIKE INITIAL PROCESS IN THE PARTNER-AFFECTIVE DEVELOPMENT OF THE CHILDREN AND GIRLS OF INITIAL Education OF THE EDUCATIONAL CENTER ROTARY CLUB MODERN MACHALA AND THE CENTER OF Education Basic PRESIDENT JAIME ROLDOS AGUILERA OF THE CIUDAD DE MACHALA, YEAR 2012. The Sciences of the Education, they have carried out a great contribution during these last years in the processes of active inter-learning, recognizing in the first place, the formation of basic competition through the systematic education in the fellows, heterogeneities exist from many points of view. Does the question arise therefore it is necessary to homogenize the educational processes using personal methodological approaches further on in the period of adaptation, if we have children that bring behavior problems and problem of family type and does it hinder its immediate adaptation in the educational processes of the initial level?. Hoping the family parents participate to try to help in the problems of the children's adaptation and girls without offense neither punishments. This training and shops to avoid the boy to be excessively sobreprotegido and to look for new techniques for his best development. This proposal, is based to the evaluations of the pursuit that after carrying out the training, it will be carried out in the Cantón Machala.